Diversity and Distribution of Natural Populations of Eucheuma J. Agardh and Kappaphycus Doty In Nusa Tenggara Barat, Indonesia - Sunarpi, Sunarpi; Ghazali, Mursal; Nikmatullah, Aluh; Lim, Phaik-Eem; Phang, Siew-Moi (Malaysian Journal of Science, 2013)
The genera Kappaphycus Doty and Eucheuma J. Agardh are amongst the most economicallyimportant seaweeds in Indonesia. Several species of Kappaphycus and Eucheuma are cultivated in many farms in Indonesia including Nusa Tenggara Barat (NTB). However the cultivated Kappaphycus is infl uenced by environmental changes. Variation in seaweed germplasm is necessary in order to produce elite lines with required quantity. More than 10 wild specimens of Eucheum/Kappaphycus species are obtained in the NTB marine waters, including E. spinosum (green and brown), E. striatum (green and brown), Eucheuma/Kappaphycus sp-1 and Eucheuma/Kappaphycus sp-2. Distribution of the species in NTB has been mapped, showing that Lombok Island has more diverse species of Eucheuma compared to Sumbawa Island. In addition, morphological and physiological characterisation of the species have been undertaken, and it is observed that there are morphological differences in the same species obtained from different coastal zones, and thus indicating morphological plasticity of the species to different environmental conditions. (Keywords: West Nusa Tenggara, E. spinosum, E. striatum, E. edulis, E. serra, natural diversity, seaweeds)